2017
DOI: 10.1175/jpo-d-16-0264.1
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Mixing in a Deep Fracture Zone on the Mid-Atlantic Ridge

Abstract: Midocean ridge fracture zones channel bottom waters in the eastern Brazil Basin in regions of intensified deep mixing. The mechanisms responsible for the deep turbulent mixing inside the numerous midocean fracture zones, whether affected by the local or the nonlocal canyon topography, are still subject to debate. To discriminate those mechanisms and to discern the canyon mean flow, two moorings sampled a deep canyon over and away from a sill/contraction. A 2-layer exchange flow, accelerated at the sill, transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(76 citation statements)
references
References 84 publications
5
70
0
Order By: Relevance
“…If the depth range corresponding to the rise of the isotherms in the direction of the jump is above the level of the upper thermistor, then shifting the more weakly stratified waters from the Southern Depression toward the sill or termination of the hydraulic control overflow would cause the temperature increase at the upper thermistor. This situation of positive correlation of the lower and upper thermistors was observed, for example, in the first half of October 2013 (Figure ). Clément et al () showed the determinative influence of spring‐neap modulation (14‐day cycle) on turbulent mixing and overflow regime in the canyon narrows/sills in the South Atlantic Ridge fractures in the Brazil basin. To illustrate the role of this modulation in the Romanche FZ, we show in Figure d the distribution of the absolute values of the total tidal velocity on the basis of TPXO 7.2.…”
Section: Mooring Observationsmentioning
confidence: 99%
“…If the depth range corresponding to the rise of the isotherms in the direction of the jump is above the level of the upper thermistor, then shifting the more weakly stratified waters from the Southern Depression toward the sill or termination of the hydraulic control overflow would cause the temperature increase at the upper thermistor. This situation of positive correlation of the lower and upper thermistors was observed, for example, in the first half of October 2013 (Figure ). Clément et al () showed the determinative influence of spring‐neap modulation (14‐day cycle) on turbulent mixing and overflow regime in the canyon narrows/sills in the South Atlantic Ridge fractures in the Brazil basin. To illustrate the role of this modulation in the Romanche FZ, we show in Figure d the distribution of the absolute values of the total tidal velocity on the basis of TPXO 7.2.…”
Section: Mooring Observationsmentioning
confidence: 99%
“…Thurnherr et al () argue that hydraulic processes associated with the subinertial along‐canyon flow passing across sills on the canyon floor contribute significantly to the elevated diapycnal mixing in the canyon. This inference has recently been confirmed by data from the Dynamics of Mid‐Ocean Ridge Experiment (DoMORE) project (Clément et al, ).…”
Section: Introductionmentioning
confidence: 61%
“…The mean abyssal flow within the canyon in the 1990s was found to be eastward based on moored current meters at 17.5°W (Thurnherr et al, ; Toole, ). More recent observations recorded by current meters and McLane Moored Profilers deployed at the sill near 14.6°W and at 13.7°W also show eastward flow below 3,900 m in 2014/2015 (Clément et al, ). The available data thus confirm persistent eastward flow within the canyon, which is essential to maintain a quasi‐steady state in the presence of strong diapycnal mixing (L. C. St. Laurent et al, ).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations